An Exploration of the Garden Architecture of Li Yu’s Novel Twelve Towers - Zhao, Wei; Tan, Yin; Xing, Fengyu; Wu, Lili (International Journal of Natural Resources and Environmental Studies, 2025)
Li Yu’s Twelve Buildings is a chapter book from the Ming and Qing dynasties uctural element. The architectural originality of the buildings depicted in the text reflects the characteristics and development of garden architecture during that historical period. This study adopts a methodological approach that extracts garden architecture genes from the text of the novel using a landscape gene extraction method. The garden architecture genes are then categorised into three types: architectural genes, elemental genes, and plaque genes. The subsequent extraction of these three levels of existing garden architecture gene elements enables the creation of garden architecture gene mapping, facilitating the restoration of the design of the novel’s Group-photo House scene. The gene map facilitates a more accurate and comprehensive reproduction of ancient garden architecture, thereby providing a method for the discovery of the characteristics of ancient Chinese garden architecture and the inheritance of garden culture.